Experimental study on partial replacement of fine aggregateby lathe steel waste with natural fibre in concrete - Pooja S Lachyan; Fajal Mohammad Shaikh; Vinayak Raghunath Patil; Saurabh Mahendra Rajguru; Om Roopchand Pawara; Ganesh Babasaheb Sathe (International Journal of Engineering and Technology, 2024)
This topic focused on bettering concrete properties by replacing traditional materials with waste products, like from the steel industry, andincorporating natural fibres. The aim of this research are to mitigating environmental hazards connected with industrial waste while improving concrete performance. The studies investigated the feasibility of using steel lathe waste as a partial replace for fine aggregate inconcrete, along with including coconut Fiber for some reason. Through experimental analysis, the percent of lathe scrap replacement andnatural fibre incorporation is determined to achieve the mechanical properties wanted. The research assesses the compressive, tensile, andflexural strengths, as well workability and consistency of the concrete mixes - important stuff. Additionally, durability and resistance toenvironmental factors are being looked at. Comparative analysis includes figuring out cost-effectiveness with traditional concrete, eventhough it might be obvious. The project's scope includes a rather comprehensive investigation into the benefits and challenges of thesealternative materials, contributing to sustainable construction practices, and minimizing environmental impact.